2020
DOI: 10.1002/acp.3687
|View full text |Cite
|
Sign up to set email alerts
|

Do you believe what you have been told? Morality and scientific literacy as predictors of pseudoscience susceptibility

Abstract: Summary The aim of the current study was to examine the antecedents of susceptibility to pseudoscientific information. Participants were asked to assess their perceived probability of and familiarity with statements containing popular science misconceptions and pseudoscientific claims, which were fabricated for the study. Measures of scientific literacy, moral inclinations, need for closure, and a set of additional variables were collected. Analysis of the results showed that susceptibility to known pseudoscie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 69 publications
(104 reference statements)
4
8
1
Order By: Relevance
“…Furthermore, various predictors (unconventional thinking, DI, and AB) were differentially associated with the acceptance of different pseudoscience topics. This is in line with previous findings (Piejka & Okruszek, 2020; Rutjens et al, 2018) and offers useful and particularized information to combat the different branches of pseudoscience. As already suggested by other authors, campaigns and interventions aimed at combating pseudoscience should be tailored to the particularities of each branch, according to its respective predictors (Rutjens et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, various predictors (unconventional thinking, DI, and AB) were differentially associated with the acceptance of different pseudoscience topics. This is in line with previous findings (Piejka & Okruszek, 2020; Rutjens et al, 2018) and offers useful and particularized information to combat the different branches of pseudoscience. As already suggested by other authors, campaigns and interventions aimed at combating pseudoscience should be tailored to the particularities of each branch, according to its respective predictors (Rutjens et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…As some authors have suggested, these discrepancies could be due to differences in the popularity of different types of pseudoscience across countries (Dekker et al, 2012). It could potentially explain the differences between the results obtained in our research (Spanish sample) and those obtained by Piejka and Okruszek (2020) (Polish sample). However, the latter study does not report the same comparison regarding the familiarity of the different pseudoscience topics; therefore future research should further investigate this possibility.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations